PENGARUH MODAL USAHA, TENAGA KERJA, DAN LAMA USAHA TERHADAP PRODUKSI KAIN ENDEK DI PROVINSI BALI - Ida Bagus Wahyu Cahaya Pratama; Ni Luh Karmini (E-Jurnal Ekonomi Pembangunan, 2023)
Hand-woven ikat fabrics made in Bali, such as endek, are generally of good quality and are traded at relatively high prices in the market. However, now more and more woven products similar to Balinese endek are made outside Bali and sold at relatively lower market prices than authentic Balinese endek. When people choose non-balinese endec fabrics, it inevitably reduces the income of genuine Balinese endec weavers as the original Balinese artisans quit their jobs. This in turn will affect production, which will continue to decline. The data analysis technique used in this study is multiple linear regression. Research results show that capital, labor force and business period simultaneously have a great impact on the production of endek fabric in Bali. Capital, labor force and duration of business also partially affect the production of endek cloth in Bali. The conclusion of this study is that an increase in capital by Endek Stov entrepreneurs leads to an increase in production. As the labor force increases, so does the resulting output. This is consistent with the Cobb-Douglas theory that capital and labor affect output. Bringing in more capital will increase production, sell more products, and ultimately increase your income. keyword: lorem Capital, Employ, Duration of the Business, Production Endek Fabric